2013
DOI: 10.1111/tpj.12232
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in CHS1, a TIRNB protein, induces chilling sensitivity in Arabidopsis

Abstract: SUMMARYLow temperature is an environmental factor that affects plant growth and development and plant-pathogen interactions. How temperature regulates plant defense responses is not well understood. In this study, we characterized chilling-sensitive mutant 1 (chs1), and functionally analyzed the role of the CHS1 gene in plant responses to chilling stress. The chs1 mutant displayed a chilling-sensitive phenotype, and also displayed defense-associated phenotypes, including extensive cell death, the accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 67 publications
2
72
0
Order By: Relevance
“…For example, overexpression of antioxidant-defensive genes enhances chilling tolerance in maize and soybean (Van Breusegem et al 1999;Kocsy et al 2001), whereas repression of catalase gene expression reduces chilling tolerance (Kerdnaimongkol and Woodson 1999). Arabidopsis chs (chilling-sensitive) mutants display increased sensitivity to chilling temperature, which is at least partially due to the excessive accumulation of H 2 O 2 in chs mutant seedlings (Huang et al 2010a, b;Wang et al 2013;Yang et al 2010). Recent studies also show that ROS act as signal molecules mediating cold stress-signal transduction.…”
Section: Aba and Ros Under Cold Stressmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, overexpression of antioxidant-defensive genes enhances chilling tolerance in maize and soybean (Van Breusegem et al 1999;Kocsy et al 2001), whereas repression of catalase gene expression reduces chilling tolerance (Kerdnaimongkol and Woodson 1999). Arabidopsis chs (chilling-sensitive) mutants display increased sensitivity to chilling temperature, which is at least partially due to the excessive accumulation of H 2 O 2 in chs mutant seedlings (Huang et al 2010a, b;Wang et al 2013;Yang et al 2010). Recent studies also show that ROS act as signal molecules mediating cold stress-signal transduction.…”
Section: Aba and Ros Under Cold Stressmentioning
confidence: 95%
“…Cold stress induces the accumulation of SA in Arabidopsis, whereas SA-deficient mutants show increased growth in response to cold (Scott et al 2004). Gain of function of R/R-like protein mutants that overproduce SA, such aschs1, chs2, and chs3, display chillingsensitive phenotypes that are partially dependent upon SA (Huang et al 2010a;Yang et al 2010;Wang et al 2013). Indeed, there appears to be an optimal threshold of endogenous SA that is crucial for the chilling-dependent inhibition of plant growth.…”
Section: Sa and Cold Stressmentioning
confidence: 95%
“…Proteins analogous to mammalian signaling adaptors, which initiate downstream pathways by homotypic interactions with receptors, have not been identified in plants (90), although plant genomes contain truncated NLR genes that might naturally serve adaptor functions in resistance (55,64). Genetic and molecular analyses have shown that two truncated forms, the Arabidopsis cytoplasmic TIR-NB protein CHS1 (chilling sensitive 1) and the related TIR-NB CHL1 (CHS1-like 1), are important for restricting TNL immunity to maintain plant growth and fitness over a range of environmental conditions (144,156). Other truncated variants produced by TNL mRNA alternative splicing promote TNL resistance once ETI is initiated (36,74,158).…”
Section: Building Receptor Signaling Complexes Nlr Homo-and Heteromermentioning
confidence: 98%
“…CHS1 encodes a truncated TIR-NB protein. A missense mutation in CHS1 results in activation of cell death and defense responses at low temperature (Wang et al, 2013; Zbierzak et al, 2013). …”
Section: Autoimmunity Caused By Gain-of-function Mutations In Nb-lrr mentioning
confidence: 99%